ABSTRAKSI FIGUR PUNOKAWANDENGAN TEKNIK STENLING (Menggabungkan Teknik StencilDan Teknik Marbling) - Zarkasi, Much. Sofwan; Sukirno, S., (Institut Seni Indoensia Surakarta, 2018)
ABSTRACTCreation of Mono PrintGraphic Art Work with Abstraction of Punokawan Figure Use STENLING Technique (Combining Stencil Technique and Marbling Technique), based on opportunities related to creativity and experimentation in graphic arts that have two-dimensional printing art character. One of them is creating mono print graphic artwork with the process of combining stencil techniques and marbling techniques. The purpose of this creation is to open opportunities as wide as possible regarding creativity in graphic art works that have been seen as having occupied the position of the second art in fine arts after painting. The method applied in the creation of this work is the method of experimentation which is the incorporation of stencil techniques and marbling techniques. The creation of monoprint graphic artwork by combining these two techniques produces monoprint graphic artwork with visuals in the form of Punokawan figure characters abstraction. It is hoped that the results of the creation of this work can be one of the innovations in graphic art both in technical and form forms so that it can elevate the prestige of the graphic artwork itself.Keywords: monoprint, combined stencil & marbling